An overview of bioactive components and phytopharmaceutical potentials of Hygrophila auriculata–A herbaceous medicinal plant - Megha Malpotra; Meenakshi Garg; Neha Singh; Susmita Dey Sadhu; Rajni Chopra; Bhupesh Sharma (Phytomedicine Plus)
The current review intends to summarize the bioactive components, nutritional profile, phytopharmaceutical properties, mechanism of action, and functional food aspects of Hygrophila auriculata. It was traditionally used to prepare ancient Indian ayurvedic medicines for treating chronic disorders. Indeed, the plant is a copious source of bioactive compounds like quercetin, ellagic acid, gallic acid, betulin, lupeol, and stigmasterol. The plant is also abundant in sodium, potassium, iron, fiber, vitamin C, and β-carotene. The bioactive compounds are linked to phytopharmaceutical properties like antioxidant, cardioprotective, anti-diabetic, diuretic, hepatoprotective, androgenic, haematinic, anti-cancer, anti-inflammatory, etc. However, more research is still needed to connect existing literature with contemporary pharmacology. The plant holds a promising future in functional food development and bio-packaging. Future research should also focus on isolating bioactive compounds from numerous parts of the plant and analyzing the mechanisms of action of such compounds.